A new species of Hemiphyllodactylus Bleeker, 1860 (Squamata: Gekkonidae) from Pulau Enggano, southwestern Sumatra, Indonesia - Grismer, L. Lee; Riyanto, Awal; Iskandar, Djoko T.; Mcguire, Jimmy A. (Zootaxa, 2014)
A new species of gekkonid lizard Hemiphyllodactylus engganoensis sp. nov. from Pulau Enggano, southwestern Sumatra, Indonesia is differentiated from all other congeners by having the unique combination of a maximum SVL of 37.3 mm; six chin scales; no enlarged postmentals; five circumnasal scales; three or four scales between the supranasals; 12 supralabials; 24 dorsal scales; 15 ventral scales; a lamellar hand formula of 4554 or 4454; a lamellar foot formula of 4555; four subdigital lamellae on the first finger; four or five subdigital lamellae on the first toe; a continuous, femoroprecloacal pore series of 42; five cloacal spurs in males; no enlarged subcaudal scales; no dark postorbital stripes or striping on body; small dark blotches on dorsum; a yellowish postsacral mark bearing anteriorly projecting arms; and a pigmented caecum and gonads. Hemiphyllodactylus engganoensis sp. nov. is part of the speciose H. typus group.